Issues of Hedge Accounting in IFRS in Consolidated financial Statement - A. Yu. Kuzmin (Учёт. Анализ. Аудит, 2019)
In consolidated accounting the reflection of the financial results of the valuation and the accounting processes can present a challenge. That requires the development of special procedures of the joint accounting of financial results of the hedging that are consistent with the provisions of IFRS.There is a typical situation, characterized by the following components: internal hedging operations initiated by subsidiaries to the parent company create open positions with different parameters for the parent company; maternal unit of the company responsible for the management of financial risks at the general group level, in order to eliminate the negative consequences of the changes of conditions for the groups in the market, can hedge transactions by buying a single forward contract with significantly different from intra-group transactions parameters.The need to develop special procedures of joint financial hedging results, consistent with the provisions of certain IFRS standards has been proven in the article. Within the limits of tasks there have been designed and documented evaluation procedures for joint accounts for hedge accounting fair value and cash flow hedging contracts groups formed as a purely financial articles, and non-financial articles. With a view to the practical implementation of the evaluation procedures there have been proposed the methods of assessment of corresponding objects of accounting as well as the aspects of hedge effectiveness criteria have been investigated.